Development of Android-Based Interactive Learning Media to Improve Student Learning Outcomes in Arabic Subjects for Grade VIII at MTsN 6 Kediri - Yulianti, Shinta Felisa; Zunairah, Yuyun; Nidak, Khoiru (Proceeding International Conference on Education, 2025)
This research was based on the low learning outcomes of students in Arabic class. One of the main reasons is the reliance on traditional and less engaging teaching methods, as well as the absence of interactive learning media. Therefore, the purpose of this study is to develop an Android-based interactive learning media and to examine its suitability, usability, and effectiveness in improving students’ learning. The research was conducted with eighth-grade students at MTsN 6 Kediri using the Research and Development (R&D) method with the ADDIE model, which consists of five steps: Analysis, Design, Development, Implementation, and Evaluation. The instruments used included observation, questionnaires, interviews, and tests, with a sample of 34 students from class VIII D. Data were analyzed using both qualitative and quantitative approaches. The results showed three main findings. First, the developed product is an Arabic learning application called ARABIKU, which provides materials, audio, videos, interactive quizzes, and practice exercises. Second, expert validation confirmed its feasibility: the material expert scored it 96.8% (very suitable), the first media expert 77.7% (suitable), and the second media expert 93.6% (very suitable). Practicality tests also indicated positive results, with 97% from the teacher (very practical) and 83% from students (very practical). Third, the effectiveness test demonstrated an improvement in learning outcomes, as the average score increased from 67.5 to 80. In conclusion, this Android-based interactive learning media is feasible, practical, and effective in improving Arabic learning for eighth-grade students at MTsN 6 Kediri